Knowledge hiding in organizations: everything that managers need to know. Issue 6 (14th June 2019) - Anand, Payal; Hassan, Yusuf
Abstract : Purpose: Though there have been umpteen discussions on knowledge sharing in organizations, there is a dearth of discussion on knowledge hiding acts, especially in learning organizations. The purpose of this paper is to introduce this novel construct "knowledge hiding" and to highlight its relevant aspects crucial to organizations. Design/methodology/approach: The paper reviews published articles on knowledge hiding and proposes four broad categories to distinguish the causes of knowledge hiding. This paper further suggests substantial measures that managers need to emphasize for dealing with the dimensions that influence knowledge hiding acts, to alleviate or mitigate the causes behind knowledge hiding acts at the workplace. Findings: This paper identifies the causes of knowledge hiding behaviors and segregates these causes under four broad categories, i.e. person-related, job-related, coworkers-related, and organization-related causes. Originality/value: This paper provides valuable information on knowledge hiding acts in the workplace to the practitioners in a simplified structure, along with some practical remedies to manage such acts.